In Silico Design And Immunoinformatics Evaluation Of A Multi-Epitope Vaccine Candidate Against Mycobacterium Tuberculosis - Maulana, Muhammad Anthony; Wasisto, Matias Aryasatya; Sricahyonoaji, Hendro Kusumo (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Tuberculosis, caused by Mycobacterium tuberculosis, continues to be a major global health threat, causing 1.3 million deaths annually despite the availability of the Bacillus Calmette–Guérin (BCG) vaccine, which offers variable efficacy in adults. The emergence of multidrug-resistant strains further highlights the need for novel vaccine strategies. In this study, an in silico immunoinformatics approach was employed as a cost-effective and safe method to design a multi-epitope vaccine candidate with enhanced immunogenic potential. Epitope prediction was performed for major M. tuberculosis antigens (Ag85 complex, CFP-10, HspX, TB10.4) using IEDB servers, yielding 95 CTL and 39 HTL epitopes. Epitopes were screened for high antigenicity (VaxiJenv2.0 > 0.4), non-allergenicity (AllerTOPv2.1), and non-toxicity (CSM-Toxin). Selected epitopes were combined using suitable linkers to construct the vaccine, and physicochemical properties were assessed with ProtParam. The 3D model was predicted and refined using I-TASSER and GalaxyRefine, validated by SAVESv6.1. The construct displayed global and Southeast Asian HLA coverages of 58.57% and 49.21%, respectively, indicating sufficient potential for global vaccine deployment. Structural analysis indicated high stability (instability index 33.27) and thermostability (aliphatic index 65.94). Molecular docking with TLR4 displayed stable interaction (lowest energy weighted score -976.8) and immune simulation displayed efficient humoral and cellular response, indicated by peak IgM and IgG titers following simulated injections, adequate activations of CTLs and HTLs, and progressive memory cell development. This study presents a promising multi-epitope vaccine candidate against M. tuberculosis. Further in vitro and in vivo validation is necessary to confirm its immunogenic potential.